International Branch Campuses and Institutional Control - Coelen, Robert (International Higher Education, 2014)
Institutions going abroad with International Branch Campuses face a significant increase in the resources required to control the delivery and quality of their mobilized programs. This extra burden finds its origin in factors related to partners, internal perceived barriers between campuses, and the additional jurisdiction.